Topology Optimization of Metallic Antennas - Hassan, Emadeldeen; Wadbro, Eddie; Berggren, Martin (IEEE transactions on antennas and propagation, 2014)
We introduce an approach to carry out layout optimization of metallic antenna parts. An optimization technique first developed for the optimization of load-bearing elastic structures is adapted for the purpose of metallic antenna design. The local conductivity values in a given region are used as design variables and are iteratively updated by a gradient-based optimization algorithm. Given a set of time-domain signals from exterior sources, the design objective is here to maximize the energy received by the antenna and transmitted to a coaxial cable. The optimization proceeds through a sequence of coarsely-defined lossy designs with successively increasing details and less losses as the iterations proceed. The objective function gradient is derived based on the FDTD discretization of Maxwell's equations and is expressed in terms of field solutions of the original antenna problem and an adjoint field problem. The same FDTD code, but with different wave sources, is used for both the original antenna problem and the adjoint problem. For any number of design variables, the gradient is evaluated on the basis of only two FDTD simulations, one for the original antenna problem and another for the adjoint field problem. We demonstrate the capability of the method by optimizing the radiating patch of both UWB monopole and microstrip antennas. The UWB monopole is designed to radiate over a wide frequency band 1-10 GHz, while the microstrip patch is designed for single and dual frequency band operation. In these examples, there are more than 20,000 design variables, and the algorithm typically converges in less than 150 iterations. The optimization results show a promising use of the proposed approach as a general method for conceptual design of near-resonance metallic antennas.